Co-circulation and co-infection of hantaviruses and Wenzhou mammarenavirus in small mammals and humans in Jiangxi, China - Du, Shanshan; Xie, Yun; Deng, Xuefei; Xia, Zhiyong; Wu, Wei; Huang, Xiaoxia; Chen, Zhao; Li, Aqian; Li, Chuan; Wang, Qin; Sun, Lina; Guo, Meijun; et al. (Frontiers in Microbiology, 2023)
A total of 461 small mammals of 7 species and paired sera from 43 suspected HFRS cases were collected from Jiangxi Province, China. Viral genomic RNA and specific antibodies against Hantavirus (HV) and Wenzhou Mammarenavirus (WENV) were detected to evaluate the epidemic situation of the two viruses. Hantaan virus (HTNV), seoul virus (SEOV) and WENV RNA were detected in the lungs of the captured mammals, which resulted 4.1% and 7.4% of HV and WENV RNA positive respectively. Co-infections of WENV and SEOV were detected from Rattus norvegicus, Mus musculus and Rattus flavipectus with an overall co-infection rate of 0.65%. The detection rates of antibodies in the blood against HV and WENV were 11.9% (55/461), and 13.2% (61/461) respectively. The prevalence of viral infection and viral genetic characters varied among the selected areas. In the paired sera of 43 suspected HFRS cases, 38 were with HV infection, 11 were with WENV IgG, and 7 with a 4-fold or more of WENV IgG titer elevation. These results revealed the fact of the co-circulating and coinfection of HV and WENV in the same area at the same time, which might impact on public health safety.